Barth’s Call for a ‘Biblical Attitude’ and Miskotte’s ‘Alphabetization’ of Theology - Marquardt, Friedrich-Wilhelm (Journal of reformed theology, 2021)
This article is an English translation of an essay originally published in the journal Zeitschrift für dialektische Theologie in 1989. In it, Friedrich-Wilhelm Marquardt revisits Karl Barth’s proposal in § 23 of Church Dogmatics that ‘biblical attitude’ is the first among several norms for Christian dogmatics. The article compares Barth’s emphasis on the ‘biblical formfulness’ of theology with the program of the Dutch Reformed theologian K.H. Miskotte, which seeks to educate Christians in the ‘iconic language’ of Scripture. It argues that Miskotte is concerned with hermeneutics in such a way that “Rudolf Bultmann’s name belongs—maybe before Barth’s—in proximity to Miskotte’s.” In contrast to Bultmann, however, Miskotte aims at teaching a language and generating speech rather than catalyzing self-understanding.